Development of a core outcome set for myocardial infarction in clinical trials of traditional Chinese medicine: a study protocol - Min Li; Jing Chen; Hongcai Shang; Ruijin Qiu; Jiayuan Hu; Ya Huang; Songjie Han; Changming Zhong; Tianmai He; Yiyi Lin; Manke Guan (BMJ Open, 2019)
Introduction Myocardial infarction (MI) is the most dangerous complication in patients with coronary heart disease. In China, there is an increasing number of randomised controlled trials (RCTs) of traditional Chinese medicine (TCM) for treating MI. However, the inconsistency of outcome reporting means that a large number of clinical trials cannot be included in systematic reviews to provide the best evidence for clinical practice. The aim of this study is to develop a core outcome set (COS) for future TCM clinical trials of MI, which may improve the consistency of outcome reporting and facilitate the synthesis of data across studies in systematic reviews.Methods and analysis We will conduct a systematic review of MI clinical trials with any intervention. Semistructured interviews will be conducted to obtain the perspectives of patients with MI. The outcomes from the systematic review and semistructured interviews will be grouped and used to develop a questionnaire. The questionnaire will be developed as a supplement for the TCM syndromes of MI and will be constructed from the results of a systematic review, existing medical records and a cross-sectional study. Then two rounds of the Delphi survey will be conducted with different stakeholders (TCM experts and Western medicine experts in cardiovascular disease, methodologists, magazine editors and patients) to determine the importance of the outcomes. Only the TCM experts will need to response to the questionnaire for core TCM syndromes. A face-to-face consensus meeting will be conducted to create a final COS and recommend measurement time for each outcome.Ethics and dissemination This project has been approved by the Ethics Committee of Dongzhimen Hospital, Beijing University of Chinese Medicine. The final COS will be published and freely available.Trial registration number This study is registered with the Core Outcome Measures in Effectiveness Trials database as study 1243 (available at: http://www.comet-initiative.org/studies/details/1243).